2017
DOI: 10.1111/ijfs.13464
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of culture conditions and development of a novel fed‐batch strategy for high production of β‐galactosidase by Kluyveromyces lactis

Abstract: Summary The aim of this study was to enhance β‐galactosidase production by Kluyveromyces lactis CICC1773. Firstly, the optimum culture conditions were obtained by response surface methodology, and the maximum β‐galactosidase activity reached 20.6 U mL−1, about two‐fold increase than that of the initial conditions (initial fermentation medium and conditions). To further improve β‐galactosidase production, a new fed‐batch strategy based on pH feedback control was developed successfully in a 7‐L fermenter, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This is well aligned with previous results reported for Nannochloropsis by Zanette et al 15 and Li et al 3 . The maximum extracellular β-galactosidase activity (40.84 ± 0.23 U L −1 ) measured in this study was similar to those secreted by other microalgae species 3 , 15 , 40 , but lower than those previously reported in other studies with bacteria and yeast 41 , 42 . Studies conducted by Suwal et al 18 and Li et al 3 reported similar patterns when cultivating Nannochloropsis on lactose-enriched standard medium, observing a peak of extracellular β-galactosidase activity roughly midway through cultivation before a sharp decrease.…”
Section: Discussionsupporting
confidence: 87%
“…This is well aligned with previous results reported for Nannochloropsis by Zanette et al 15 and Li et al 3 . The maximum extracellular β-galactosidase activity (40.84 ± 0.23 U L −1 ) measured in this study was similar to those secreted by other microalgae species 3 , 15 , 40 , but lower than those previously reported in other studies with bacteria and yeast 41 , 42 . Studies conducted by Suwal et al 18 and Li et al 3 reported similar patterns when cultivating Nannochloropsis on lactose-enriched standard medium, observing a peak of extracellular β-galactosidase activity roughly midway through cultivation before a sharp decrease.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we obtained lactase activity of 146.04 U/mL in a 5 L fermenter, which is 1.31-fold higher than that of the previously reported non-recombinant K. lactis CICC1773 in a 7 L fermenter (111.61 U/mL) [ 8 ]. However, lactases from K. lactis are intracellular enzymes, leading to high costs in downstream processing, including the cell disruption and separation steps.…”
Section: Discussionmentioning
confidence: 50%
“…S7 ). pH is an important factor affecting lactase production, as it influences the electrical properties of the plasmalemma [ 8 ]. The lactase activity of K. lactis JNXR-2101 increased gradually when the pH was changed from 4.5 to 6.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation